Pengaruh Mediasi Orangtua Terhadap Afinitas Televisi dan Lama Menonton Televisi Pada Anak - Nina Mutmainnah Armando; Hendriyani Hendriyani (Atma Jaya Indonesia Catholic University, Jakarta, 2012)
This study explains how parental mediation, mothers’ and fathers’, inﬂ uences television afﬁ nity and usage among children. Survey data of Jakarta-based 5 grade elementary school children (N = 188) reveal that level of parental mediation, in term of restrictive and active, tends to be high, while level of coviewing tends to be low. However, only mothers’ restrictive mediation and fathers’ restrictive mediation correlate positively with television afﬁ nity; active mediation and coviewing do not inﬂ uence children’s television afﬁ nity signiﬁ cantly. There is no direct correlation between any types of parental mediation with television usage. This study also ﬁ nds that television afﬁ nity correlates signiﬁ cantly with television usage. It seems that the more restriction of watching television they have, the more attractive the medium for the children. However, those with high afﬁ nity tend to have low television usage, most probably because they are only allow watching television for a certain period at home. On the contrary, children with low TV afﬁ nity spend a lot of time watching television. Thus, even though television is a dominant medium in children life, it is not treasured by the children; it is just wallpaper in the house for them.